2017
DOI: 10.1002/app.45373
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, mechanical, and rheological properties of graphite‐ and graphene oxide‐filled biodegradable polylactide/poly(ɛ‐caprolactone) blend composites

Abstract: The effect of graphite (G) and graphene oxide (GO) dispersions on the thermal, mechanical, rheological properties of biodegradable polylactide (PLA)/poly(E-caprolactone) (PCL) blend composites has been comparatively investigated. Surface morphology analysis indicates that the degree of morphological stability depends on not only the loading of the filler but also enthalpic interaction between the filler surface and the polymer blend. A significant improvement in the elongation at break (43.8%), with well-balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…In summary, lower activation energies to that of G‐filled blend composites were obtained for GO‐filled blend composites with high crystallization ability and electrical resistivity (poor electrical conductivity), whereas the G‐filled blend composites show significant improvement in the electrical conductivity. This behavior is further attributed to the surface morphology characteristics which were reported by Botlhoko et al . In brief, it was noted that the presence of GO particles reduced the droplets sizes of the domain PCL phase from 1.3 to 0.5 μm due to the loading effects and the enthalpy interaction of the particles and blend matrices.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…In summary, lower activation energies to that of G‐filled blend composites were obtained for GO‐filled blend composites with high crystallization ability and electrical resistivity (poor electrical conductivity), whereas the G‐filled blend composites show significant improvement in the electrical conductivity. This behavior is further attributed to the surface morphology characteristics which were reported by Botlhoko et al . In brief, it was noted that the presence of GO particles reduced the droplets sizes of the domain PCL phase from 1.3 to 0.5 μm due to the loading effects and the enthalpy interaction of the particles and blend matrices.…”
Section: Resultsmentioning
confidence: 59%
“…GO was prepared through the chemical oxidation of natural G powder as per the improved Hummers method reported by the Tour and coworkers . Further details on GO synthesis can be found in the Supporting Information . The graphite, here, was used without any chemical or thermal treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, blending PP and LDPE is not always expected to result in improvement of the impact strength of PP owing to the immiscibility between PP and LDPE. Recently, a number of studies have shown that incorporating nanofillers and copolymers into polymer blends can improve the compatibility between blended polymers, and one such filler is montmorillonite (MMT) nanoclay. Pure MMT is incompatible with most organophilic polymers and leads to poor dispersion of silicate layers in the composites.…”
Section: Introductionmentioning
confidence: 99%